Bacterial protein MakA causes suppression of tumour cell proliferation via inhibition of PIP5K1α/Akt signalling - Eric Toh; Palwasha Baryalai; Aftab Nadeem; Kyaw Min Aung; Sa Chen; Karina Persson; Jenny L. Persson; Bernt Eric Uhlin; Sun Nyunt Wai (Cell Death and Disease, 2022)
Abstract Recently, we demonstrated that a novel bacterial cytotoxin, the protein MakA which is released by Vibrio cholerae, is a virulence factor, causing killing of Caenorhabditis elegans when the worms are grazing on the bacteria. Studies with mammalian cell cultures in vitro indicated that MakA could affect eukaryotic cell signalling pathways involved in lipid biosynthesis. MakA treatment of colon cancer cells in vitro caused inhibition of growth and loss of cell viability. These findings prompted us to investigate possible signalling pathways that could be targets of the MakA-mediated inhibition of tumour cell proliferation. Initial in vivo studies with MakA producing V. cholerae and C. elegans suggested that the MakA protein might target the PIP5K1α phospholipid-signalling pathway in the worms. Intriguingly, MakA was then found to inhibit the PIP5K1α lipid-signalling pathway in cancer cells, resulting in a decrease in PIP5K1α and pAkt expression. Further analyses revealed that MakA inhibited cyclin-dependent kinase 1 (CDK1) and induced p27 expression, resulting in G2/M cell cycle arrest. Moreover, MakA induced downregulation of Ki67 and cyclin D1, which led to inhibition of cell proliferation. This is the first report about a bacterial protein that may target signalling involving the cancer cell lipid modulator PIP5K1α in colon cancer cells, implying an anti-cancer effect.